A CASE OF PARAGANGLIOMA AND CYANOTIC CONGENITAL HEART DISEASE: A RARE CO-OCCURENCE - K, Malathi; AW, Norasyikin; S, Norlela; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Pheochromocytoma and paraganglioma (PPGL) are rare neuroendocrine tumors. Cyanotic Congenital heart Disease (CCHD) refers to a collective of heart defects presenting at birth with low level of oxygen in the blood leading to chronic hypoxemia. An association between these two rare diseases has been reported in several case studies. CASE A 23-year-old female presented with a history of postbidirectional cardiopulmonary shunt at the age of 6 for dextrocardia, atrioventricular canal defect and pulmonary stenosis. She had further complications of chronic hypoxemia, secondary polycythemia, cavernous sinus thrombosis and type 2 diabetes mellitus. During followup, the patient was found to present with persistent elevation of blood pressure with the triad of palpitations, headaches and diaphoresis. Catecholamine hypersecretion was suspected. Twenty-four hour urine catecholamines revealed norepinephrine 548.2 µg/day [normal value (NV) 12.1 to 85.5], epinephrine 11.6 µg/day (NV 1.7 to 22.4) and dopamine 233 µg/day (NV <496.1). She had no hypertensive retinopathy, but had proteinuria with an estimated glomerular filtration rate of 60 mL/min/1.73 m2. Thyroid function tests were normal. Other tests showed elevated haemoglobin (20.8 g/dL), low pO2 (51.2 mmHg) and an Hba1c of 7%. Abdominal computerised tomography showed a left large oval paraaortic mass consistent with a paraganglioma with no features suggesting metastasis. After extensive discussion, due to the high-risk procedure and financial limitations, surgery was rejected and the patient family opted for medical treatment. She was treated with rivaroxaban 20 mg OD, prazosin 2 mg TDS, metoprolol 100 mg BD, atorvastatin 40 mg OD, aspirin 100 mg OD and sitagliptin + metformin 50 mg/500 mg OD. Her blood pressure is stable. CONCLUSION CCHD patients are at higher risk to develop PPGL due to chronic hypoxia that increases angiogenic factors leading to tumour development. Therefore, active screening and early treatment for PPGL by biochemical or radiological methods may be beneficial for CCHD patients. Clinicians should continue a long-term follow-up to monitor PPGL recurrence if hypoxia is not corrected. Further research is needed for better understanding and revealing the deeper pathogenic connection between hypoxia and PPGL.